How do you evaluate -4^{-3+}2^{0}?

1 Answer
Nov 28, 2017

See a solution process below:

Explanation:

First, use this rule of exponents to rewrite the 2 term:

a^color(red)(0) = 1

-4^-3 + 2^color(red)(0) => -4^-3 + 1

Next, use this rule of exponents to rewrite the 4 term:

x^color(red)(a) = 1/x^color(red)(-a)

-4^color(red)(-3) + 1 => -1/4^color(red)(- -3) + 1 =>

-1/4^color(red)(3) + 1 => -1/64 + 1

Now, put each term over a common denominator to add the terms:

-1/64 + (64/64 xx 1) => (-1)/64 + 64/64 => (-1 + 64)/64 = 63/64